Enhancing the training integrity of human service staff using pyramidal behavioral skills training. Issue 1 (13th July 2019) - Erath, Tyler G.; DiGennaro Reed, Florence D.; Sundermeyer, Hunter W.; Brand, Denys; Novak, Matthew D.; Harbison, Matt J.; Shears, Rick
Abstract : This experiment used a pyramidal training model to evaluate the effects of behavioral skills training (BST), delivered in a 1‐time group‐training format, on the extent to which 25 human service staff implemented BST when training others how to implement behavioral procedures. Results indicated that (a) the training workshop increased BST integrity to mastery levels for the majority of participants with varying levels of education, organizational positions, and training experience, (b) the training effects generalized to teaching an untrained skill, and (c) high levels of BST integrity maintained at follow‐up 4 to 6 weeks after training for all 3 participants with whom probes were conducted. Moreover, participants indicated high levels of satisfaction with both the training workshop and BST as a training procedure.